51.2k views
2 votes
3(2x - 1) = 1/2 (4x - 2) + 2
What would it be?

2 Answers

4 votes

Answer:


3(2x - 1) = 1 / 2(4x - 2) + 2 \\ 3 * 2x - 3 * 1 = .5 * 4x - .5 * 2 + 2 \\ 6x - 3 = 2x - 1 + 2 \\ x \: togather \\ 6x - 2x = - 1 + 2 + 3 \\ 4x = 4 \\ x = 4 / 4 \\ x = 1

User Michael Gorsuch
by
5.7k points
4 votes

Answer:

X = 1

Explanation:

Just distribute properly, and distribute the fraction multiplying the numerator by 4 and 2

User Shieldfoss
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.